APPLICATION OF CONSTRUCTIVISM–BASED STUDENTS’ WORKSHEET TO INCREASE STUDENTS ACTIVITIES AND LEARNING OUTCOMES - Susilawati, Susilawati; Copriady, Jimmy; Erna, Maria; Hasnah, Hasnah; Nisa, Nurul Aulia; Rahmatya, Okma (JTK (Jurnal Tadris Kimiya), 2020)
Information gained from lecturers of organic chemistry study program in chemical education Riau University, student activities and learning outcomes are still relatively low. The researchers believe that contructivism -based students’ worksheet as a new learning method is needed to overcome the problem. The study was conducted using the application of contructivism-based students worksheet in organic chemistry II subject to increase students activities and their learning outcomes.The data were collected by observation and test. Statistics descriptive qualitative and quantitative were used to analyze the data. The data of learning outcomes were analyzed by Shapiro- Wilks normality, Wilcoxon hypothesis test and paired samples test. The result showed that average values of student activity for each subject namely aldehyde-ketones, carboxylic acids, amines and free radicals were at 37%, 37%, 30%, 36%. The result from wilcoxon and paired samples test, with significant test 0,000 < 0,05 showed that student learning outcomes on organic chemistry II subject by constructivism-based students’ worksheet was improved, It can be seen from average value of the pre-test and post-test were at 19.77; 72.15, respectively.